Pelatihan Literasi Digital Berbasis Moderasi Beragama Pada Generasi Milenial Kota Sungai Penuh Dan Kabupaten Kerinci - Karim, M; Syafrul, Syafrul Antoni; Pranata, Revo; Hanifa, Alia (Institut Agama Islam Negeri Kerinci, 2023)
Indonesia's diverse society demands a tolerant attitude. However, it is a paradox in Indonesia's diverse society that the emergence of intolerant attitudes, radicalism and extremism, especially those targeting the millennial generation, is very worrying, for this reason it is necessary to build a moderate understanding. From this background, researchers are interested in examining socio-culturally based religious moderation in the millennial generation in the city of Sungaifull and Kerinci district. This has a serious impact on their behavior in social and state life, such as producing a millennial generation that is less tolerant, even tends to be radical, and in some cases is involved in terrorist organizations. The results of the service imply the belief that the millennial generation has a big responsibility in equipping them with a moderate attitude. In many cases, the millennial generation attending educational institutions has been exposed to radical views because their teachers or religious teachers teach the concept of anti-tolerance for certain reasons. This service uses the Participatory Action Research (PAR) method, where the actors act as facilitators or companions. This aims to encourage the management of educational institutions in Sungai Penuh City and Kerinci Regency to promote and encourage the millennial generation and their alumni to develop a moderate Muslim mindset.